2023
DOI: 10.1155/2023/3806121
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Smart Grid Security Based on Blockchain with Industrial Fault Detection Using Wireless Sensor Network and Deep Learning Techniques

Manivel Kandasamy,
S. Anto,
K. Baranitharan
et al.

Abstract: Low-cost monitoring and automation solutions for smart grids have been made viable by recent advancements in embedded systems and wireless sensor networks (W.S.N.s). A well-designed smart network of subsystems and metasystems known as a “smart grid” is aimed at enhancing the conventional power grid’s efficiency and guaranteeing dependable energy delivery. A smart grid (S.G.) requires two-way communication between utility providers and end users in order to accomplish its aims. This research proposes a novel te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…The study provided simulation findings that showed how the suggested strategy might enhance the precision and dependability of IoT health systems. Refs [17,18] proposed an Internet-of-Things (IoT)-enabled data-fusion method for sleep-healthcare applications that integrates data from multiple sources including wearable devices, smartphones, and environmental sensors. The proposed method uses a deep learning-based approach to extract features from the raw data and generate sleep-related metrics.…”
Section: Data Fusion For Healthcare Data Security In Iotmentioning
confidence: 99%
“…The study provided simulation findings that showed how the suggested strategy might enhance the precision and dependability of IoT health systems. Refs [17,18] proposed an Internet-of-Things (IoT)-enabled data-fusion method for sleep-healthcare applications that integrates data from multiple sources including wearable devices, smartphones, and environmental sensors. The proposed method uses a deep learning-based approach to extract features from the raw data and generate sleep-related metrics.…”
Section: Data Fusion For Healthcare Data Security In Iotmentioning
confidence: 99%